1998
DOI: 10.1677/joe.0.1590239
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endotoxin lipopolysaccharide administration on the somatotropic axis

Abstract: The aim of this work was to study the effect of chronic activation of the immune system on the somatotropic axis. Accordingly, the changes in growth hormone (GH) secretion, circulating insulin-like growth factor-I (IGF-I) and IGF binding proteins (IGFBPs) in response to endotoxin lipopolysaccharide (LPS) administration were examined in adult male Wistar rats. Acute LPS injection (2·5, 25 or 250 µg/kg) increased serum corticosterone in a dosedependent manner and decreased serum levels of insulin and IGF-I, seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 44 publications
6
61
0
3
Order By: Relevance
“…Studies have reported that inflammatory cytokines can directly act on central nervous system, reducing the secretion of the growth promoting hormone such as GH and IGF-1 (Hasselgren 1993;Soto et al 1998), and eventually affect the growth performance of animals. In this study, LPS stimulation significantly reduced the serum GH and IGF-1 content, which in line with the previous studies.…”
Section: Growth Performancementioning
confidence: 99%
“…Studies have reported that inflammatory cytokines can directly act on central nervous system, reducing the secretion of the growth promoting hormone such as GH and IGF-1 (Hasselgren 1993;Soto et al 1998), and eventually affect the growth performance of animals. In this study, LPS stimulation significantly reduced the serum GH and IGF-1 content, which in line with the previous studies.…”
Section: Growth Performancementioning
confidence: 99%
“…Endotoxin administration in rats increases plasma concentrations of corticosterone, whereas it decreases circulating IGF-I and its gene expression in the liver (Soto et al 1998, Defalque et al 1999. The adult liver is the main source of circulating IGF-I and its main serum-binding protein, IGF-binding protein-3 (IGFBP-3), which are synthesized by different cell populations.…”
Section: Introductionmentioning
confidence: 99%
“…Serum IGF-I was removed from IGFBPs by an acidethanol extraction and was measured by a double-antibody RIA (Soto et al 1998). The IGF-I antiserum (UB-2495) was a gift from Drs Underwood and Van Wyk, and was distributed by the Hormone Distribution Program of NIDDK (Bethesda, MD, USA) through the National Hormone and Pituitary Program.…”
Section: Hormone Measurementsmentioning
confidence: 99%
“…Western blots were prepared as previously described (Soto et al 1998). Blood serum proteins were separated by 12·5% SDS-PAGE under non-reducing conditions and blotted onto nitrocellulose membranes (Hybond-C-extra; Amersham, Little Chalfont, Bucks, UK) by means of a semidry electrophoretic transfer cell (Bio-Rad, Hercules, CA, USA).…”
Section: Western Ligand Blotmentioning
confidence: 99%
See 1 more Smart Citation